Geohazard-Seismic: Qualitative and Quantitative Risk Analysis based on Seismic Attribute at Bujang Field, Malay Basin - HASNI, NORAZIF ANUAR (2021)
Sedimentary rock deposition occurs in very fast rates in offshore basin and might cause a shallow subsurface geohazards that will incur high risk and cost of drilling operations